2019
DOI: 10.29407/jmn.v2i1.13124
|View full text |Cite
|
Sign up to set email alerts
|

Analisa Dasar Proses Pengolah Sampah Plastik Bekas Menjadi Bahan Bakar Alternatif Dengan Proses Pirolisis

Abstract: Penelitian ini dilatarbelakangi oleh semakin banyaknya sampah plastik yang sulit terurai. Sampah plastik menjadi sebab munculnya berbagai permasalahan, seperti: sumber penyakit, pencemaran tanah, pencemaran air, dan jika dibakar menjadi pencemaran udara yang sangat berbahaya bagi yang menghirupnya. Belum adanya cara pengolahan sampah plastik yang tepat menjadi masalah yang serius kedepan. Upaya pemanfaatan kembali (Reuse) hanya berguna untuk memperpanjang masa pakai, tetapi tidak mengurangi jumlah sampah yang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Mixing biomass in the cracking of plastic waste will restrict the development of residual carbon [9]. A study on the processing a mixture of PP plastic waste and palm kernel shell waste using pyrolysis has been carried out and showed that the highest conversion was obtained at 350°C [10]. Therefore, the addition of biomass with low volatile matter content, such as empty palm fruit bunches (EPFB) may increase the yield of catalytic cracking of PP plastic waste.…”
Section: Introductionmentioning
confidence: 99%
“…Mixing biomass in the cracking of plastic waste will restrict the development of residual carbon [9]. A study on the processing a mixture of PP plastic waste and palm kernel shell waste using pyrolysis has been carried out and showed that the highest conversion was obtained at 350°C [10]. Therefore, the addition of biomass with low volatile matter content, such as empty palm fruit bunches (EPFB) may increase the yield of catalytic cracking of PP plastic waste.…”
Section: Introductionmentioning
confidence: 99%